System reconfiguration ontology to support model‐based systems engineering: Approach linking design and operations - Qasim, Lara; Hein, Andreas Makoto; Olaru, Sorin; Garnier, Jean‐Luc; Jankovic, Marija (Systems engineering, 2023)
System reconfiguration is essential in complex systems management, as it is an enabler of system flexibility and adaptability. It ensures system operation and increases reliability, availability, maintainability, testability, safety, and reuse of system entities and technologies. For the reconfiguration of a system in use, it is necessary to assess, in continuity, the system's state with regard to its context. Identifying data supporting system reconfiguration represents a major industrial challenge and is linked directly to the development of industrial reconfiguration tools. Reconfiguration tools are based on a data model, also called ontology, which represents key concepts of system reconfiguration and their relationships. A particular difficulty of developing the data model is the multi‐domain nature of reconfiguration. Furthermore, it needs to address a considerable diversity of system types. Few publications propose an ontology supporting data identification and tool development for the entire process. Hence, in this paper we propose to formalize the system reconfiguration process and propose an overarching ontology, which we call OSysRec. This ontology considers data at the management, dynamics, and structure level. The proposed ontology has been developed based upon expert knowledge and several industrial uses cases. The OSysRec ontology allowed a better understanding of the reconfiguration process, and hence it can be deployed for developing efficient and effective reconfiguration tools at the industrial scale. The ontology has been tested on an industrial case study to validate the proposed approach.